ONOMATOPE DALAM LAGU ANAK-ANAK BERBAHASA INDONESIA - Khairunnisa Khairunnisa; Hermandra Hermandra; Nursal Hakim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this study is to describe type, structure and function of onomatopeia in Indonesian children’s songs. Type of this study is qualitative study and explain the result study according to descriptive. Results of the analysis showed that in Indonesian children’s songs there are three types of onomatopeia that is (1) type of onomatopeia that imitate the sound of the object, (2) type of onomatopeia that imitate the sound of the animal, and (3) type of onomatopeia that imitate the human’s feeling. Structure of onomatopeia in Indonesian children’s songs classification based on syllables that is (1) monosyllables, (2) bisyllables, and (3) multisyllables. Function of onomatopeia in Indonesian children’s songs there are three function that is (1) function of onomatopeia showed that imitate the sound of the object, (2) function of onomatopeia showed that imitate the sound of the animal, and (3) function of onomatopeia to give effect for listener songs.Keyword: children’s songs, onomatopeia